Good enough to eat : a study of cannibalism in literature and film in the twentieth century - Brown, Jennifer (Trinity College (Dublin, Ireland). School of English, 2010)
This thesis is an examination of the cannibal figure in 19th and 20th century literature and film. The cannibal transgresses boundaries of normality and morality and is thus considered Other. As a transgressor of boundaries, the cannibal evokes horror and repulsion. As such, the label of cannibal has been used throughout history to denigrate a given individual or group. My argument is that by examining who is labelled cannibal in any given time, we can understand the fears and prejudices of society at that time. I examine the cannibal chronologically in different genres in order to show this sense of movement through the century.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin